Green tribology assessment: A Comprehensive review of bio-lubricants and nano enhancers - Amirmahdi Rahmani; Hesam Khadem Razavi; Masoud Dehghani-Soufi (Energy Conversion and Management: X)
The pursuit of sustainable lubrication solutions has led to significant research efforts in the development of bio-lubricants, aligned with green tribology principles, to mitigate environmental impact and enhance industrial efficiency. Nonetheless, the major setbacks such as food competing for the same vegetable oils resources, high costs of sourcing the raw materials, and difficulties in the application of nano additives have limited the extent of bio-lubricants usage. In this review, recent advancements in bio-lubricant production, focusing on chemical modifications to improve the thermal stability, oxidation resistance, and performance characteristics of vegetable oils are explored. Additionally, using nanoparticles as nano enhancers in bio-lubricants is examined for their potential to reduce friction and wear. The tribological performance of nano enhanced bio-lubricants is evaluated, highlighting their effectiveness in enhancing viscosity, reducing friction coefficients, and improving wear resistance. This paper also argues that it is necessary to improve the purity and dispersion of bio-lubricants to make them more economically viable for the performance. Finally, the incorporation of bio-lubricants with petroleum-based alternatives and implementation of eco-friendly nanomaterials is suggested to foster sustainable development in lubricant manufacturing without compromising economic aspects.